Identification and prioritization of pigeon pea‐based products tailored to consumer preference perspective: A mixed method assessment approach. Issue 3 (27th January 2022) - Majili, Zahra; Nyaruhucha, Cornelio N.; Kulwa, Kissa; Mutabazi, Khamaladin; Rybak, Constance; Sieber, Stefan
Abstract: Pigeon pea is frequently consumed in Southern Tanzania but in limited value‐added recipes. The aim of this study was to identify and prioritize pigeon pea‐based products that could be developed to improve organoleptic preferences and increase the diversification of the recipes. A descriptive cross‐sectional study was conducted involving 355 consumers. Quantitative and qualitative information was collected through focus group discussions (FGDs) and face‐to‐face interviews. Pairwise comparison (PC) method and assigning scores in order of their preference was used in ranking pigeon pea‐based products at the group and individual levels, respectively. PC counts and Garrett rank scores were computed and ranked using the Rank command in Excel software Version 2016. Ordinal regression was used to summarize the effect between groups' overall levels of the outcome at p ‐value < 0.05. Twelve and eleven pigeon pea‐based products were identified during face‐to‐face interviews and FGDs, respectively. The highest Garret mean scores were observed on pigeon pea‐based noodles (70.6), flour (61.4) and chapati (60.4). Similarly, the highest PC counts were observed on pigeon pea‐based noodles and chapati. The PC rank scores differed significantly by consumers' age categories. Pigeon pea‐based noodles, flour and chapati are the utmost prioritized products due to their perceived value, sensory attributes, convenience and attitudes about the food product. However, knowledge and skills about using pigeon peas on producing the product were mentioned as limiting factors. Hence, the provision of practical hands‐on skills on the preparation of pigeon pea‐based products will increase the chances of diversifying pigeon pea recipes at the household level for improving food security and nutrition well‐being.